Organisation, Financing, and Implementation of Preconception Care in Primary Care: Implications for Women’s Health and Well-Being - Lora Draeva; Eleonora Hristova-Atanasova; Georgi Iskrov; Rumen Stefanov (Healthcare, 2026)
(1) Background: Preconception care (PCC) is an important component of preventive reproductive healthcare and public health because modifiable risk factors affecting maternal, neonatal, and longer-term health may be present before conception. Despite broad recognition of its potential value, substantial uncertainty remains regarding how PCC should be organised, financed, and implemented across different healthcare systems. (2) Methods: This structured narrative review synthesised evidence on healthcare- provider models, financing, affordability, willingness to pay (WTP), and barriers and facilitators affecting PCC implementation. A structured search of PubMed, Scopus, and Web of Science Core Collection covered publications from January 2010 to March 2026 and was updated on 14 July 2026. Original research studies, systematic and scoping reviews, narrative reviews, clinical guidelines, policy reports, and relevant methodological or health-economic publications were considered. A structured qualitative appraisal was used to interpret evidence according to study design or evidence type, directness to PCC, healthcare-system context, methodological limitations, and consistency across sources. A total of 61 publications were retained in the structured evidence synthesis. (3) Results: No single PCC delivery model was consistently supported as universally applicable. Across heterogeneous settings, the evidence more consistently supported broad principles including accessibility, continuity of care, multidisciplinary coordination, clear professional roles, financial accessibility, and integration with existing healthcare pathways. Implementation was constrained by insufficient training, consultation-time limitations, unclear professional responsibilities, fragmented service organisation, inadequate reimbursement, and socioeconomic inequalities. Evidence on WTP, specific financing arrangements, and digital delivery models was more limited and context-dependent. (4) Conclusions: The available evidence supports PCC as an important preventive reproductive-health strategy, but the optimal organisational and financing models remain uncertain and are likely to depend on healthcare-system context. Integrated and multidisciplinary approaches appear promising, although specific provider configurations, financing mechanisms, and digital interventions require further comparative and longitudinal evaluation. The author-developed hypothetical conceptual model proposed in this review should therefore be interpreted as a hypothesis-generating synthesis of the available evidence rather than as an empirically validated clinical pathway or causal model.